2000
DOI: 10.1177/153857440003400624
|View full text |Cite
|
Sign up to set email alerts
|

Noonan's Syndrome Associated with Spontaneous Rupture of the Ascending Aorta

Abstract: Noonan's syndrome associated with spontaneous rupture of the ascending aorta is rare. Review of the literature reveals only one such reported case. The authors describe a 41-year-old male with Noonan's syndrome who initially presented with lower extremity claudication. Computed tomography and digital subtraction angiography disclosed an abnormal dilation of the ascending thoracic aorta and a distal abdominal aortic dissection. The patient underwent successful aortoiliac bypass graft. Seven months later, he suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A literature review revealed a few case reports of aortic aneurysm at the aortic root or ascending aorta in NS (Table 1). 917 For the other, rarer RASopathies, one case of aortic root aneurysm in an adolescent with Costello syndrome was identified. 18 The combination of clinically relevant aortic issues in several NS patients and evidence suggesting the involvement of MAPK pathways in the development of aortic aneurysms led us to investigate the prevalence of aortic dilation in NS patients using a retrospective study design.…”
mentioning
confidence: 99%
“…A literature review revealed a few case reports of aortic aneurysm at the aortic root or ascending aorta in NS (Table 1). 917 For the other, rarer RASopathies, one case of aortic root aneurysm in an adolescent with Costello syndrome was identified. 18 The combination of clinically relevant aortic issues in several NS patients and evidence suggesting the involvement of MAPK pathways in the development of aortic aneurysms led us to investigate the prevalence of aortic dilation in NS patients using a retrospective study design.…”
mentioning
confidence: 99%